EFEKTIVITAS IMPLEMENTASI ALAT PERAGA KOTAK GAYA GESEK TERHADAP KETERAMPILAN PROSES SAINS SISWA - Kamariyah; Haris; Budiyono (Postgraduate, University of Mataram, 2023)
This research was conducted to determine the effectiveness of the implementation of the friction force box teaching aid on students' science process skills. The research subjects were class X students of MA Miftahul Ulum Bettet Pamekasan. This type of research is experimental research with the one group pretest-posttest design method. Increasing students' science skills (KPS) can be analyzed using the normal gain test, which is equal to 0.55 in the moderate category. This shows that the friction force box teaching aid can improve students' KPS. In addition, an analysis of student responses was carried out in using the friction style box teaching aid which showed that the teaching aid was very suitable for use in the learning process.